2005
DOI: 10.1021/ma0477549
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Proton Conductivity of Partially Sulfonated Poly([vinylidene difluoride-co-hexafluoropropylene]-b-styrene) Block Copolymers

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
202
5
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 204 publications
(221 citation statements)
references
References 51 publications
12
202
5
2
Order By: Relevance
“…This observation agrees with the experimental data for P(VDF-co-HFP)-b-SPS diblock copolymer membranes where the activation energy is reported to fall from 25.7 to 17.1 kJ/mol as IEC increases from 0.72 to 1.18 mmol/g. 56 As shown previously in the TEM images, membranes with lower IEC form smaller, more isolated ionic clusters; thus, the energy barriers for both water swelling and proton motion are greater.…”
Section: Resultssupporting
confidence: 58%
“…This observation agrees with the experimental data for P(VDF-co-HFP)-b-SPS diblock copolymer membranes where the activation energy is reported to fall from 25.7 to 17.1 kJ/mol as IEC increases from 0.72 to 1.18 mmol/g. 56 As shown previously in the TEM images, membranes with lower IEC form smaller, more isolated ionic clusters; thus, the energy barriers for both water swelling and proton motion are greater.…”
Section: Resultssupporting
confidence: 58%
“…Measurements performed on both series show that the conductivities are comparable for similar IEC. Results from Shi and Holdcroft 23,25 are reproduced in Figure 16; the samples studied by SANS are indicated on the figure by large circles (series 2) or squares (series 1). The conductivity of membranes from series 1 appears to level off and even decrease at high IEC.…”
Section: Summary Of Structures Observed By Sans and Waxsmentioning
confidence: 96%
“…Tangential proton conductivity at room temperature and at 100% RH was measured by ac impedance spectroscopy with a HP 8753A network analyzer, using a frequency range of 300 kHz to 1 GHz and a gold-plated coaxial probe 23 and using Nafion as a standard sample. The protocols used to measure and calculate the number of water molecules per ionic site, λ value, and the ion exchange capacity, IEC, of the whole molecule, are presented in the refs [23][24][25]. The fluorous block number-average molecular weight, M n , was measured using a gel permeation chromatograph, GPC, using three µ-Styragel columns, a Waters 510 HPLC, polystyrene standards, THF eluant, and a Waters 410 differential refractometer.…”
Section: Block Copolymer Synthesis and Membrane Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfonated poly(aryl ether ketone) copolymers based on 4,4'-(hexafluoroisopropylidene)diphenol, 1,3-bis(4-fluorobenzoyl)benzene and disulfonated difluorobenzophenone have good thermal and oxidative stability [211]. Amphiphilic block copolymers comprising sulfonated poly(vinylidene difluoride-co-hexafluoropropylene)-b-polystyrene were synthesized having moderately low polydispersity index [212,213]. Transmission electron microscopy studies suggested interconnected networks of ion channels, each 8-15 nm wide and the conductivity was of the same order as that of Nafion.…”
Section: Transport Of Ions and Protons Within Self-assembled Polymer mentioning
confidence: 99%